Photocatalytic degradation of dye using CeO2/SCB composite catalysts - Duangdao Channei (2018)
© 2017 Elsevier B.V. The main task of the present work is to enhance the photocatalytic degradation efficiency of methylene blue (MB) by using CeO2/sugarcane bagasse (SCB) composite catalysts. Homogeneous precipitation method was used to synthesis CeO2-SCB composite catalysts by adding SCB powder to precursor solution of Ce base-metal. The structural analytical data indicated the pure cubic fluorite structure of CeO2. Morphological images revealed the coating of CeO2layer on high surface area of SCB core-shell. The chemical analysis presented spectrum of the Ce 3d in CeO2/SCB sample existed in the form of the Ce3 +and Ce4 +mixed- valence states. Optical spectra showed the shift of absorption edge towards longer visible region upon supporting CeO2with SCB. The main chemical composition of the SCB was K, Ca, and Si. Furthermore, recombination of the photogenerated electrons and holes was identified by photoluminescence techniques (PL), the data suggested inhibition of electron—hole pairs recombination by the cations from SCB loaded in CeO2/SCB composite. Photocatalytic activity of CeO2/SCB catalyst was investigated via the degradation of MB under UV-A irradiation. Experimental kinetic data followed the pseudo-first order model. CeO2supported with SCB adsorbent had higher photocatalytic activity in dye wastewater treatment compared to the pure CeO2. The proposed mechanism explaining the high photocatalytic efficiency of CeO2/SCB was associated with high surface properties and the suppression of recombination of the photogenerated electron-hole pairs by the SCB adsorbent.